2021
DOI: 10.5152/cjms.2021.3188
|View full text |Cite
|
Sign up to set email alerts
|

Disease and Treatment Experiences of COVID-19 Patients: A Qualitative Study

Abstract: BACKGROUND/AIMSThe study aimed to explore the perceptions of hospitalized COVID-19 patients' experiences regarding the disease and treatment process. MATERIAL and METHODSThe study was carried out as qualitative research at a hospital in Turkey between June 17, 2020 and July 7, 2020. The sample consisted of eight COVID-19 patients hospitalized in service after intensive care treatment. The data were collected through an in-depth individual interview form. Each interview was transcribed verbatim, and a thematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Regarding the identification of feelings experienced during hospitalization , 71.9% (n = 23) of the articles indicated that the patients and family members experienced difficult moments 47 during the hospitalization period, with feelings of loneliness 16,17,21,31 and isolation 16,17,21,29,31,40,41 due to the restrictions regarding visits and companions and a lack of contact between professionals and patients 20 . Feelings such as sadness, 23,26,46 fear, 17,18,20,22,24–29,32,33,46 anxiety, 17,22,28,38,41,46 worry, 17,20–24,32,33,46 nervousness, 22 guilt, 26,46 anger, 23,26 tiredness, 24 hopelessness, 46 frustration, 43 discrimination, 18,22 vulnerability, 29,32,46 and uncertainty 22 were also reported, associated with lack of knowledge about the disease and with the situation in which they found themselves. It is noted that the articles described concerns about the personal 21 or family 20 socioeconomic situation as aggravating factors, because of uncertainty of the economic and housing situation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the identification of feelings experienced during hospitalization , 71.9% (n = 23) of the articles indicated that the patients and family members experienced difficult moments 47 during the hospitalization period, with feelings of loneliness 16,17,21,31 and isolation 16,17,21,29,31,40,41 due to the restrictions regarding visits and companions and a lack of contact between professionals and patients 20 . Feelings such as sadness, 23,26,46 fear, 17,18,20,22,24–29,32,33,46 anxiety, 17,22,28,38,41,46 worry, 17,20–24,32,33,46 nervousness, 22 guilt, 26,46 anger, 23,26 tiredness, 24 hopelessness, 46 frustration, 43 discrimination, 18,22 vulnerability, 29,32,46 and uncertainty 22 were also reported, associated with lack of knowledge about the disease and with the situation in which they found themselves. It is noted that the articles described concerns about the personal 21 or family 20 socioeconomic situation as aggravating factors, because of uncertainty of the economic and housing situation.…”
Section: Resultsmentioning
confidence: 99%
“…As for welcoming of the team during hospitalization , 68.8% (n = 22) of the articles addressed how the team was treated, highlighting attitudes of kindness, 17,31 empathy, 17,28 courtesy, 25 respect, 25,45 sympathy, 28,29 understanding, 29 compassion, 31 professionalism, 24,31 communication, 21 and attention and patience 34 . Attitudes like these were associated with an improvement in the patients’ state of mind 17 and with a sense of security, 18,23,46 making a difference to patient satisfaction 28–31 . Furthermore, in one of the studies, 94.7% of the patients reported having received support from the maternity team 37 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations